Frontier Zones and the Study of Religion - Birgit Meyer (Journal for the Study of Religion)
This articlefocuses on the concept of the frontier zone as a central critical term in Chidester’s oeuvre. Understood as a site where difference is articulated, encountered,and governed, the frontier zone is a productive, insight-generating notion. Its usefulness pertains not only to the study of colonial settings in which scholarly knowledge aboutreligion in Africa took shape via the introduction of religion as a category,but also to the study of religious Birgit Meyer58plurality in contemporary European cities, which is here proposedto approach as new postcolonial frontier zones.